Comparison of different methods of determining power output in weightlifting exercises - Hori, N.; Newton, R. U.; Nosaka, K.; McGuigan, M. R. (Strength and Conditioning Journal, 2006)
Measurement of power output during weightlifting movements provides useful information about an athlete`s performance. However, there are various methods used,each with specific considerations, advantages, and disadvantages.This article discusses the methods of measuring power output in weightlifting exercises in these terms. In summary, coaches can use either a force platform or a position transducer to measure power output in weightlifting exercises. However, they should be cognizant of the limitations and assumptions of each method. In calculation of power in weightlifting exercises, only barbell mass should be used when a position transducer is used. On the other hand, when a force platform is used, both barbell mass and the lifter's body mass should be used. Both methods are logical and valid, and by using one or both of these methods, coaches can monitor the athletes' power output capability at any external load. However, additional investigation of the validity of these methods is needed. If power outputs are measured at several different external loads, maximum power output and optimal load can be obtained. By observing these values, coaches can monitor how athletes respond to training programs over a long period. .